PECULIARITIES OF THE FORMATION OF NOUNS WITH THE HELP OF COMPOSING IN MODERN CHINESE - Sadullaevna, Yusupova Hilola (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the peculiarities of the formation of nouns using a composing model of word formation in modern Chinese. The article analyzes several types of compositional models, such as: synonymous, antonymic, summarizing, generalizing, and special type. In the study, methods such as analysis, synthesis, and component analysis were used. The article provides relevant conclusions on this topic.